Automatic classification of infant cry: A review - Saraswathy, J.; Muthusamy, Hariharan, Dr.; Sazali, Yaacob, Prof. Dr.; Wan Khairunizam, Wan Ahmad, Dr, (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/